Perioperative intensive glycemic control for liver transplant recipients to prevent surgical site infection: A systematic review and meta‐analysis. Issue 6 (16th August 2020) - Oliveira, Ramon Antônio; Poveda, Vanessa de Brito; Tanner, Judith
Abstract: Background: Surgical Site Infections (SSIs) are common among liver transplant recipients and result in adverse patient outcomes. Standard glycemic control is effective in reducing SSIs. Some studies suggest intensive glycemic control reduces the risk of SSI further. Methods: For this systematic review, were searched for studies comparing perioperative intensive and standard glycemic control in liver transplant recipients. Clinical trials registries and reference lists of included studies were also searched. No date or language restrictions were applied. Randomized controlled trials (RCTs) were assessed using Cochrane risk of bias tool and GRADE method. Cohort studies were assessed using the Newcastle‐Ottawa Scale. Results: Two RCTs and three cohort studies met the inclusion criteria. Low‐quality evidence from the two RCTs in a meta‐analysis with 264 recipients found it was uncertain whether the risk of SSI was reduced by having intensive glycemic control (Risk Ratio [RR] 1.52, 95% CI 0.66‐3.51). However, there was an increased risk of hypoglycemia among recipients having intensive glycemic control (RR 2.34, 95% CI 1.40‐3.92) n = 264. Meta‐analyses found it uncertain whether secondary outcomes, allograft rejection and death, were reduced among recipients having intensive glycemic control; (RR 0.85, 95% CI 0.48‐1.50) and (RR 0.92, 95% CI 0.44‐1.95), respectively. The two cohort studies were poor quality and presented conflicting outcomes on the effects of intensive blood glucose control on SSI. Conclusion: There is insufficient evidence to recommend the use of intensive glycemic control among liver transplant recipients to reduce SSIs.